Physical activity and its relationship with COVID-19 cases and deaths: Analysis of U.S. counties - Cunningham, G. B. (Journal of Sport and Health Science, 2021)
Purpose: The study was to examine county-level associations of physical activity with coronavirus disease (COVID-19) cases and deaths, per 100,000 county residents. Methods: Data were collected from publicly available data sources for 3142 counties and equivalents, including the District of Columbia. Subjective health ratings, percentage uninsured, percentage unemployed, median household income, percentage female residents, percentage White residents, percentage of residents age 65 or older, and rural designation served as controls. Results: The two-level random intercept regression showed that physical activity rates at the county level were statistically and negatively associated with COVID-19 cases and deaths. Additional analyses showed that physical activity rates moderated the relationship between cases and deaths, such that the relationship was strongest when physical activity rates were low. Conclusion: The results presented here offer empirical evidence of the benefits of county-level physical activity during a pandemic. Implications for public health and physical activity provision are discussed.